The Influence of Maintenance and Quality Control on Quality Product - Fathur Darajat Surahman; Dudi Haryadi (Almana : Jurnal Manajemen dan Bisnis, 2021)
Product quality is the most important part that makes a product acceptable and meets consumer wants and needs. The company has two programs to ensure the quality of these products, namely by carrying out maintenance (preventive maintenance and corrective maintenance) and quality control during the production process. The purpose of this study was to determine how the maintenance, quality control, and product quality implemented by PT. Samase Clothes. And to find out how much influence maintenance on product quality, the effect of quality control on product quality, and the effect of maintenance and quality control on product quality. This study is sample research in which employees, staff, and production admins are respondents in the study, for data collection using a questionnaire with the number of respondents 65 people. The analytical method used is a quantitative method with descriptive analysis and verification analysis. To process data, the author uses the help of Microsoft Excel 2016 and SPSS 25 For Windows. The results showed that maintenance was in the good enough category, quality control was in the good enough category, the product quality was in the good enough category.